“La cineantropometria en las habilidades específicas para la práctica del baloncesto en adolescentes de la Unidad Educativa San Felipe Neri 2017-2018” - Bonilla Delgado, Jorge Luis (2018)
The present research project called "Cineantropometry in the specific skills for the practice of basketball in adolescents of the San Felipe Neri Educational Unit 2017- 2018.” is presented as a field research, quasi-experimental, being a quantum-quantitative research of type cross. The sample was constituted by 10 adolescents of the selection of the infantile category and 10 students who belong to the tenth course of the San Felipe Neri Educational Unit, constituting two research groups: intervention group are conformed by the basketball athletes, and the control group It is made up of a group of students of the same age. The main objective of this research project is to determine the influence of cineanthropometry on the performance of specific skills in basketball practice in adolescents. As an instrument of the present investigation, the Naveta test and an anthropometry film evaluation were used; a four-week intervention was carried out, during which time an intervention program was applied based on the development of specific skills; evidencing at the end of the same the significant improvement of test two (throwing under the basket) p = 0.05. In addition, it was noted that the largest population of athletes of this educational instruction has an endomorphic somatotype. So it is recommended that coaches and monitors be prepared at the time of taking the test both in specific skills and also in the taking of cineantropometry from early adolescents